PENGARUH KEMAMPUAN MERESPON TUTURAN TUTOR DAN PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN BERBICARA WARGA BELAJAR PAKET C DI SKB KENDAL - Hapsari, Melati Indri; Sholekhah, Bibit (JIV-Jurnal Ilmiah Visi, 2009)
This research aimed at discovering the effects of ability to respond the tutor’s narration and mastery of vocabulary to speaking skill of Package C students in Kendal Learning Activity Cente(LAC). The research population covered the Package C students of the second grade. Sampels were selected randomly and a set of test was used to collect the data to be analysed statistacally. The findings show that the ability to respond the tutor’s narration and vocabulary mastery give significant contribution to the speaking ability of the Package C students in Kendal LAC. Based on the findings, the research recommends narrative approach model as one of the techniques in learning vocabulary.